A career in the academic society of the USA. (Journal of Educational Sciences, 2016)
There is a consideration of the main aspects of construction of the academic career in the United States of America and broad opportunitiesof grants for scientifi c research in the present article. The mechanisms of training of the higher qualifi cation scientifi c staff in the USA have been studied. A postdoctoral study in the USA is being understood as work on research and teaching in the universities, serves for career promotion in the academic society. It is shown that for getting the fi nal goal it is necessary to make the best that is the postdoctoral study supposes a serious work with problems, periods, supervisor and reports about the work. It is strictly forbidden to make a scientifi c career in the own university where the candidate gets a scientifi c degree. The postdoctoral research breathes new life into the academic life of the universities and enriches scientifi c and educational programs. Postdoctoral fellows are scientifi c associates, developing new ideas and projects and combining research and pedagogical activity, usually they get scholarship or wage.
Keywords: Postdoctoral study; postdoctoral fellow; academic career; the USA